Comparison of Model-Free and Model-Based Dynamic Contrast-Enhanced Magnetic Resonance Imaging Pharmacokinetic Parameters for Predicting Breast Cancers' Response to Neoadjuvant Chemotherapy. Issue 2 (March 2020) - Lv, Guangjie; Zhou, Yiming; Zheng, Dandan; Gao, Jiayin; Xu, Zhujin; Jiang, Lei
Abstract : Objective: To prospectively compare the performance of model-based and model-free dynamic contrast-enhanced (DCE) pharmacokinetic parameters in monitoring breast cancers' early response to neoadjuvant chemotherapy (NACT). Methods: Sixty patients, with 61 pathology-proven breast cancers, were examined using DCE magnetic resonance imaging before, after the first cycle, and after full cycles of NACT. Both model-based ( K trans and others) and model-free parameters, mainly time-intensity curve (TIC), were measured. According to Miller-Payne grading, patients were divided into response and nonresponse group. Mann-Whitney U test, Fisher exact test, multivariate logistic regression, and receiver operating characteristic curve were used in analysis. Results: After the first cycle, among all the parameters, K trans and TIC were strongly associated with tumors' early response. There was no significant difference between the areas under receiver operating characteristic curve of K trans and TIC (0.768, 0.852, respectively). Conclusions: Model-based and model-free DCE parameters, especially K trans and TIC, have similar performance in predicting the efficacy of NACT for breast cancers.